SPECTROPHOTOMETRIC DETERMINATION OF AMOXICILLIN INPHARMACEUTICAL PREPARATIONS THROUGH DIAZOTIZATIONAND COUPLING REACTION - Al-Uzri, Wasan (Iraqi Journal of Science, 2024)
Two simple, rapid and sensitive spectrophotometric methods have beendeveloped for the determination of amoxicillin (AMX) in pure form andpharmaceutical preparations. The proposed methods are based on a couplingreaction between AMX and diazotized p-amino benzoic acid or diazotizedprocain in alkaline medium to form an intense yellow, water-soluble dyes thatare stable and have a maximum absorption at 435 nm using diazotized p- aminobenzoic acid and 450 nm on using diazotized procain. The calibration graphswere linear over the concentration rangs of 0.4 to 10 5g mL-1 and 0.4 to 14 5gmL-1 with a limit of detection (LOD) of 0.1877 5g mL-1 and 0.1916 5g mL-1,molar absorbtivity of 1.914×104 L mol-1cm-1 and 2.544×104 L mol-1cm-1 ,Sandell<s sensitivity of 21.912×10-3 5g ml-1 and 16.486 ×10-3 5g ml-1 fordiazotized p-amino benzoic acid and diazotized procain, respectively. Theproposed methods were successfully applied to the determination of AMX incapsules and injections.